2010
DOI: 10.4244/eijv6i5a98
|View full text |Cite
|
Sign up to set email alerts
|

Mesh covered stent in ST-segment elevation myocardial infarction

Abstract: Based on this experience, the MGuard stent implantation in STEMI patients is safe and highly effective. A larger randomised trial is warranted to confirm the clinical endpoints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…Moreover, when a LTB is present, the use of special mesh-covered stents can be useful in managing thrombi and preventing distal embolization. There are some small studies reporting on the use of the MGuard stent in STEMI setting, documented promising surrogate results, such as a better ST-resolution and a higher post-procedural TIMI 3 flow rate, when compared to standard types of stents [95][96][97][98] .…”
Section: Embolic Protection Devicesmentioning
confidence: 99%
“…Moreover, when a LTB is present, the use of special mesh-covered stents can be useful in managing thrombi and preventing distal embolization. There are some small studies reporting on the use of the MGuard stent in STEMI setting, documented promising surrogate results, such as a better ST-resolution and a higher post-procedural TIMI 3 flow rate, when compared to standard types of stents [95][96][97][98] .…”
Section: Embolic Protection Devicesmentioning
confidence: 99%
“…28 Similarly, among 57 patients treated with the MGuard stent during primary PCI for STEMI, cardiac mortality at mean follow-up of 38.7±3.1 months was 7.0%, with a major adverse cardiovascular and cerebral event rate of 8.8%. 20 As expected, the 12-month rates of ischemic TLR and TVR in the MGuard group were higher than in the control stent group, as the control group consisted of patients treated with DES as well as with BMS. The 8.6% and 11.0% 1-year TLR and TVR rates with the MGuard in the present study are similar to those observed with this device in the firstin-human study (11.1% TVR), 15 20 likely because of inclusion of longer and more complex lesions in the present trial.…”
Section: Discussionmentioning
confidence: 62%
“…However, longer term clinical and angiographic follow-up is needed to characterize late vascular responses to the MGuard stent, especially as the only prior study with late follow-up after MGuard stent implantation was nonrandomized. 20 We herein report the 1-year clinical and 13-month angiographic outcomes from the MASTER study.…”
Section: Mesh-covered Stent In Stemimentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should evaluate the impact of multiple stent implantations in patients treated with new stents designs (i.e. mesh covered stents, self-expandable stents), specifically for lesions with a large thrombus burden [21]. Due to growing interest in bioresorbable vascular scaffold implantation in patients with ACS, it is also necessary to assess the impact of multiple bioresorbable vascular scaffolds implantation during primary PCI on long-term clinical outcomes of patients with STEMI [22,23].…”
Section: Discussionmentioning
confidence: 99%